Implementasi Green Accounting Pada UG Technopark Sebagai Wujud Green Campus Berkelanjutan - Dini Andriyani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to analyze how companies identify, recognize, measure, present, and disclose environmental costs in financial reports. This research is a qualitative research. The data used in the UG Technopark research are primary data and secondary data. Primary data was taken from interviews and secondary data was taken from the company's financial statements. Data analysis in this study used descriptive qualitative, namely comparing the theory of the application of environmental costs according to Hansen Mowen and the application of adjustments to financial statements based on the Conceptual Framework of Financial Statements (KKLK). The results of the study show that UG Technopark in recognizing environmental costs has not implemented a grouping of environmental costs. Then the measurement of environmental costs uses the appropriate monetary units issued based on the realization of the previous period's budget. Disclosure of environmental problems in financial reports has not been specifically regulated in UG Technopark's financial reports, so that their application is in accordance with each company's policy.